Financial Management Supporting Islamic Education at SMP Bina Muda and Smp Al Ma’soem In Bandung - Riyanti, Triska; Safwandi N, Mulyawan (AIM: Journal of Islamic Education Management, 2024)
The educational facilities at SMP Bina Muda and SMP Al Ma’soem in Bandung are crucial components in achieving learning achievements. However, the availability of representative educational facilities faces challenges such as insufficient funds, the creativity of managers in seeking funding sources, and suboptimal management. These two schools, as part of their efforts to meet representative educational facilities, optimize the utilization of Zakat, Infaq, Sadaqah, Waqf (Ziswaf), and Corporate Social Responsibility (CSR) for educational financing. This qualitative research focuses on the planning, implementation, and supervision of educational facilities financing, as well as the supporting, inhibiting factors, and the impact of such financing on learning achievements in both schools. A descriptive analysis method is employed to explore the management of Islamic education financing, using management theory, education financing theory, and learning achievement theory as the theoretical framework. The research findings indicate that both schools have systematic plans for educational facilities financing, involving foundations for building investments and schools for financing learning media facilities. Monthly supervision includes the receipt of BOS funds from the government, the integrity of management, supportive facilities, and the effective utilization of Ziswaf and CSR as supporting factors. On the other hand, delays in fund disbursement and payments by parents, dependence on foundation policies, and delays in reporting are inhibiting factors. Overall, the financing of educational facilities in both schools has a positive impact on students' learning achievements